Functional characterization of nicotinic receptors in amacrine cells of rat retina - Gumilar, Fernanda Andrea (2008)
Amacrine cells are a heterogeneous class of interneurons that modulate the transfer of the light signals through the retina. The cholinergic system present in these neurons is involved in such modulation. However, the characterization of nicotinic cholinergic receptors (AChRs) in amacrine cells and their possible roles during the retina development remain unknown. In this study, we have identified functional AChRs in amacrine cells and determined their effects on neurite outgrowth using amacrineenriched cultures obtained from rat retinae. Amacrine cells were identified by their morphology and by immunocytochemical techniques using the monoclonal antibody HPC-1. We measured function of AChRs by electrophysiological studies and by confocal microscopy combined with the Ca2-+-sensitive fluorescent indicator Fluo-3/AM. Our results show that a7 AChRs are present in amacrine cells. The level of expression, measured by rhodamine-labelled a-bungarotoxin, increases in a time-dependent manner during culture. Maximal expression levels are achieved at days 8-9. Amacrine cells were examined with whole-cell recording techniques. Two different types of responses to ACh are observed after day 8 in culture: a slow-decay current (td = 111 +15 ms), and a fast-decay current (td = 11 = 2 ms). The latter one probably corresponds to functional a7 AChR, since this receptor shows fast desensitization and since the currents are inhibited by the specific antagonist, a-bungarotoxin. Given that a7 is highly permeable to calcium ions, we also assessed [Ca2+]i oscillations with Fluo3-AM induced by nicotinic agonists. When cells are exposed to ACh or nicotine, Ca2+ influx is detected as an increase in the fluorescence intensity. a-Bgt inhibits this signal, again indicating functional a7 AChRs. Interestingly, the presence of nicotine significant increases neuritic length of cultured amacrine cells. This outgrowth effect is abolished by co-treatment with a-B gt. In conclusion, amacrine cells have functional o7 receptors which may have a role in retinal synaptogenesis